Forgotten Legacy of Saṃmitīya School - Bajracharya, Surendra Man (Journal of Buddhist Studies (T.U.), 2024)
Buddhist history shows that Saṃmitīya school has been an influential Buddhist sect in the past. On the one hand, it stood unique, holding an unconventional view like pudgalavāda, which seemingly appears against anātmavāda; on the other, it remained dominant in many places as a significant branch of early Buddhism. It regarded pudgala as bhāra-hāra, the burden bearer of pañca-skandha, the building blocks of life. Nevertheless, many Buddhists viewed pudgala as an Atman and rejected it, for to be a Buddhist is not to accept the existence of Ātma translated as soul. Saṃmitīya’s influence can also be noticed in Nepal. The paper delves into revealing the legacy of Saṃmitīya and tracing its existence in Nepal.